Chemical composition, nutritional, functional and pasting properties of yellow root cassava grits and african yam bean flour blends - Victoria Funmilayo Abioye; Ololade Abosede Olodude; Bolanle Aishat Akinwande (International Journal of Food Studies)
The effect of African Yam Bean (AYB) flour substitution on the nutritional, functional and pasting properties of yellow root cassava grits was investigated. Cassava grits were obtained by peeling, washing, cutting (5.5 cm thickness in cubes), soaking (72 h, 28±2 °C), dewatering, roasting (120 °C, 20 min), sieving and milling. Roasted AYB flour was obtained by cleaning, roasting (190 °C, 10 min), dehulling, milling and sieving (425 μm). Simple lattice design was used to generate different formulations, 100:0; 90:10; 80:20; 70:30; 60:40 and 0:100 of cassava grits and AYB flour, respectively. These were analyzed for chemical composition, amino acid profile, minerals, functional and pasting properties. Total ash, protein, β-carotene and hydrogen cyanide were in the ranges of 2.16-2.66%, 2.72-20.43%, 1.33 to 3.97 µg/g and 0.07-4.47 mg/kg, respectively. Total essential amino acids and total non-essential amino acids were in the ranges of 32.51-40.18% and 59.82-67.48%. Potassium, calcium, magnesium, iron, copper, zinc, manganese and sodium of the blends ranged from 338.00-646.75, 188.00-508.00, 358.00-532.50, 59.25-140.00, 0.12-0.19, 1.07-1.71, 7.25-38.25, 25.25-161.50 mg/100 g, respectively. Bulk density, water absorption capacity, swelling capacity and swelling index ranged from 0.67-0.81 g/ml, 151.05-503.29 g/ml, 1.67-5.68 g/g and 2.86-13.32%, respectively. The blends of yellow root cassava grits and African yam bean flour could provide nutritious food formulations and offer good potential for food security.